SISTEM PENUNJANG KEPUTUSAN PENERIMA BANTUAN DESA DI KECAMATAN KLUNGKUNG DENGAN METODE SAW - Ni Kadek Sukerti (IIB Darmajaya, 2014)
Community based development program is a government program to alleviate poverty. This program funds the community in a village in economic activity to create jobs or job opportunities, capital, and also business development. CBD is running well in Bali because of the facilitators who continuously administer this program. However, it is necessary to have a system that can help the facilitators to select the beneficiaries of CBD program. One of the villages that propose to be the beneficiary is Klungkung village. This research objective is to build a decision support system using Simple Additive Weighting (SAW) method with assessment criteria include the houses condition of the village, income of each family in the village, education, and the natural condition of the village. The stages of this research are data collecting, interview and observation, analysis, design, implementation, and testing. This research results a decision support system to help the decision makers to select the beneficiaries of the program fund.Keywords: Decision Support System, Beneficiary, SAW